Strategi Dinas Komunikasi dan Informasi dalam Meningkatkan Pelayanan Informasi Kepada Masyarakat di Kabupaten Aceh Tenggara - Ahda , Alhadi; Soefi , Roezaini; Hasan, Muridha (Journal of Economics, Bussiness and Management Issues, 2025)
The Communication and Informatics Agency (DISKOMINFO) is engaged in communication, informatics, cryptography, and statistics. This study aims to evaluate information technology governance to determine the capabilities of DISKOMINFO of Southeast Aceh Regency. This study uses a qualitative descriptive method with an interview approach as the primary data collection technique. The survey results indicate that measuring the performance of information technology governance is needed to provide recommendations for improvement. The recommendations include strategic steps to improve capabilities through optimizing activities that have not been appropriately implemented. With these recommendations implemented, the target level of capability can be increased gradually to reach the maximum value at each level. This improvement in information technology governance not only supports the internal operations of DISKOMINFO but also positively impacts public services in Southeast Aceh Regency. This study is an essential reference for agencies to continue adapting and developing according to the digital era's demands.